2022
DOI: 10.3390/ijms23042076
|View full text |Cite
|
Sign up to set email alerts
|

Gel-Based Proteomic Identification of Suprabasin as a Potential New Candidate Biomarker in Endometrial Cancer

Abstract: Endometrial cancer (EC) is the most frequent gynaecologic cancer in postmenopausal women. We used 2D-DIGE and mass spectrometry to identify candidate biomarkers in endometrial cancer, analysing the serum protein contents of 10 patients versus 10 control subjects. Using gel-based proteomics, we identified 24 candidate biomarkers, considering only spots with a fold change in volume percentage ≥ 1.5 or intensity change ≤ 0.6, which were significantly different between cases and controls (p < 0.05). We used Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…With regard to statistical validation, this was performed by two proteomic studies (two-thirds/one-third cross-validation (115); leave-one-out-cross-validation (113) and four metabolomic studies (127,128,136,142). Data on differentially expressed proteins was also confirmed experimentally using alternative methodologies like dot-blot (115), IHC (119,121), RNA/qRT-PCR (117,119), western blotting (110,117), in vitro functional studies (117,121) or using existing databases and repositories (119,121).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to statistical validation, this was performed by two proteomic studies (two-thirds/one-third cross-validation (115); leave-one-out-cross-validation (113) and four metabolomic studies (127,128,136,142). Data on differentially expressed proteins was also confirmed experimentally using alternative methodologies like dot-blot (115), IHC (119,121), RNA/qRT-PCR (117,119), western blotting (110,117), in vitro functional studies (117,121) or using existing databases and repositories (119,121).…”
Section: Discussionmentioning
confidence: 99%
“…Three proteomics studies using serum (109)(110)(111) were performed by an Italian group. In 2021, the authors performed a pilot study using the serum of 15 EC patients and 15 [non-cancer patients (109)] and identified 16 proteins with diagnostic potential (Supplementary Table S7), four of which (ITIH4, CLU, SERPIN1, and C1R) were validated by western blotting.…”
Section: Blood Proteomicsmentioning
confidence: 99%
“…Multi-omics approaches allowed us to understand several tumor mechanisms and, of note, the identification of diagnostic and prognostic markers [ 24 ]. The proteomic approach allowed for the identification of several candidate biomarkers in the serum of EC patients, such as CLU, C1R, and SERPINC1 [ 25 ], SBSN [ 26 ], and PAK1 [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of circulating biomarkers may allow for easy detection, avoiding invasive sampling procedures. Thanks to a proteomic study, we recently identified new putative biomarkers in the sera of EC patients (namely SBSN [ 19 ], CLU, SERPINC1, ITIH4, C1R [ 20 ], GAL-9, GAL-1, MMP7, FASLG, and COL9A1 [ 21 ]).…”
Section: Introductionmentioning
confidence: 99%